Selective potential of herbicides in cowpea (Vigna unguiculata (L.) Walp.) under semi-arid climate conditions (Research, Society and Development, 2022)
In view of the importance of knowing the selectivity of herbicides in the cowpea culture, and the search to take to the producer the maximization in the control of weeds. The objective of this work was to evaluate phytotoxicity with the application of the herbicide fomesafen, 250 g L-1 in doses of 15.0 and 7.5 g L-1 and fluasifope-p-butyl, 250 g L-1, in doses of 20, 0 and 10.0 g L-1, arranged in a completely randomized design (DIC) with five treatments and five repetitions and applied to the cowpea culture, as a control, experimental units were maintained without herbicide application. Plant height, stem diameter, number of flowers, number of pods, green matter, dry matter were evaluated. The herbicide fomesafen was the one that caused the greatest phytotoxicity in cowpea plants, prolonging the crop cycle and interfering in the height of the plants, with no influence on the characteristics of green mass, dry mass, number of flowers, number of pods and stem diameter. At 35 DAA, doses of 7.5 g L-1 and 15 g L-1 of fomesafen and of the herbicide fluazifop-p-butyl 10 g L-1 and 20 g L-1 showed similar averages, and the control, occurring to the recovery of the plants after application. The herbicide fomesafen provided phytotoxicity to the cowpea culture in the two doses applied, while the plants of the fluazifop-p-butyl treatment did not show symptoms, regardless of the applied dose. Only the herbicide fomesafen interfered with the height of cowpea plants.